2020
DOI: 10.1093/europace/euaa147
|View full text |Cite
|
Sign up to set email alerts
|

Randomized study defining the optimum target interlesion distance in ablation index-guided atrial fibrillation ablation

Abstract: Aims While the CLOSE protocol proposes a maximally tolerable interlesion distance (ILD) of 6 mm for ablation index ablation index-guided atrial fibrillation (AF) ablation, a target ILD has never been defined. This randomized study sought to establish a target ILD for ablation index-guided AF ablation. Methods and results Consecutive patients scheduled for first-time pulmonary vein (PV) isolation (PVI) were randomly assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“…They reported that PVI with this protocol enabled high first-pass PVI ratio per PV pair (98%) with high rate of freedom from atrial tachyarrhythmia recurrence at 12 months after the index procedures (92.3%) in patients with paroxysmal AF. Hoffmann et al 15 also described that ablation with a smaller interlesion difference facilitated higher first-pass PVI rate than ablation with a larger interlesion difference in ablation J o u r n a l P r e -p r o o f index-guided PVI.…”
Section: Factors For Continuous and Deep Lesion Formationmentioning
confidence: 99%
“…They reported that PVI with this protocol enabled high first-pass PVI ratio per PV pair (98%) with high rate of freedom from atrial tachyarrhythmia recurrence at 12 months after the index procedures (92.3%) in patients with paroxysmal AF. Hoffmann et al 15 also described that ablation with a smaller interlesion difference facilitated higher first-pass PVI rate than ablation with a larger interlesion difference in ablation J o u r n a l P r e -p r o o f index-guided PVI.…”
Section: Factors For Continuous and Deep Lesion Formationmentioning
confidence: 99%
“…Our mean ITD for gap‐related tags was 5.3 mm, which is within the range advised by the CLOSE protocol. Hoffman et al very recently recommended to aim for ITD of 3.0–4.0 mm, rather than 5.0–6.0 mm, to optimize FPI based on results of a randomized controlled trial 23 . These data highlight that optimal VS thresholds can vary depending on ITDs and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Although benchmark studies have reported the safety, efficacy, clinical applicability, and procedural efficiency outcomes associated with the use of VS, 15‐22 these studies have recommended definitive VS thresholds while providing relatively general guidance on the inter‐tag distance (ITD), which is expected to influence lesion contiguity and PVI durability. A recent randomized controlled study reported that lower target ITD was associated with better acute procedural outcomes, suggesting that smaller ITDs may allow for less extensive ablation per lesion 23 . Therefore, the efficacy of PVI with lower target ITD and VS values should be validated.…”
Section: Introductionmentioning
confidence: 99%
“…This study of 42 patients randomized to both approaches was terminated early due to the superiority of the shorter ILD protocol for first-pass PVI (90.9% vs. 35%; p < 0.0001) with a shorter procedure time. 36 The combination of objection lesion representation parameters as described can be combined with other ablation strategies such as HPSD. As the formula for the AI incorporates CF, power, and time in a weighted formula, by increasing the power, a shorter time of ablation would be required for an equivalent lesion, with standard AI targets shown to have favorable results with this strategy.…”
Section: Ablation Index Force-time Integral and Interlesion Distancementioning
confidence: 99%
“…This study of 42 patients randomized to both approaches was terminated early due to the superiority of the shorter ILD protocol for first-pass PVI (90.9% vs. 35%; p < 0.0001) with a shorter procedure time. 36 …”
Section: Lesion Durabilitymentioning
confidence: 99%